Formulation of Candesartan Cilexetil Nanoparticles by Ionotropic Gelation Method Using Ultrasonication - Bisht, Tanuja; Bolmal, UB; Nainwal, Nidhi (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: Candesartan Cilexetil (CC) is a common drug used by patients suffering from hypertension and heart diseases. However, CC has poor oral bioavailability as it belongs to Biopharmaceutical Classification System (BCS) class II and has low aqueous solubility. This research work is focused to enhance the Bioavailability of CC using nanotechnology. Therefore, CC nanoparticles were developed using the ionic gelation procedure and ultrasonication. Materials and Methods: This work is aimed to formulate CC-alginate nanoparticles using the ionic gelation method and to investigate the influence of ultrasonication on the particle size and stability of nanoparticles. This work is also focused on the use of polysaccharides (sodium alginate) for nanoparticle preparation by ionic gelation technique using a cross-linking agent (calcium chloride). The physico-chemical properties, morphology, and effect of ultrasonication on particle size, as well as the effect of polymer concentration on particle size and drug release, of CC nanoparticles, were investigated. Results and Discussion: The prepared CC nanoparticles, were stable and have mean particle sizes ranging from 210-538 nm. The encapsulation efficiency of the prepared nanoparticles was reported between 67-83%. The optimized formulation was tested for its physical stability at 8°C and 25°C for 3 months. Pluronic F-68 (PF-68) was also found to have a crucial role in the long-term stability of the formulation. It was observed that sodium alginate played a pivotal role in providing sustained drug release up to 24 hr from the formulation. Conclusion: The results suggested that ultrasonication and polymer concentration leads to variation in the particle size and the homogeneity of the system.
Keywords: Candesartan cilexetil; Ionic gelation; Ultrasonication; Sodium alginate; Pluronic F-68